Harmful effects of the environment xenobiotics on the human body - Golovkova, T.A. (Актуальні проблеми транспортної медицини, 2016)
Chemical aggression of industry-related contamination of the environment, according to experts, is a leading risk-factor for population health. Ecological situation in industrial regions is characterized by a negative influence on the residents of widespread toxicants – heavy metals. The article presented analyzes data of complex researches, devoted to sanitary diagnostics of the environment. In order to assess the influence of lead and cadmium of industry-related origin on the organism of susceptible populations there was carried out analysis of the content of these metals in the environmental objects; biomonitoring in blood and urine of pregnant women – residents of the industrial city of Dnipropetrovs’k; determination of value of their total daily intake; calculation of conversion coefficients to characterize the possible relationship between external and internal exposures of xenobiotics. Хімічна агресія техногенного забруднення середовища існування людини, на думку фахівців, є провідним фактором ризику для популяційного здоров’я населення. Екологічна ситуація в промислових районах, характеризується негативним впливом на мешканців розповсюджених токсикантів важких металів. У зв’язку з цим, у роботі проаналізовані дані комплексних досліджень, присвячених гігієнічної діагностики навколишнього середовища. З метою оцінки впливу свинцю і кадмію техногенного походження на організм чутливих верств населення проведено: аналіз вмісту цих металів в об’єктах довкілля; біомоніторинг в крові та сечі вагітних жінок жительок промислового міста Дніпропетровська; визначеня величини їх сумарного добового надходження; розрахування коефіцієнтів конверсії для характеристики можливих взаємозв’язків зовнішніх і внутрішніх експозицій ксенобіотиків. Химическая агрессия техногенного загрязнения среды обитания человека, по мнению специалистов, является ведущим фактором риска для популяционного здоровья населения. Экологическая ситуация в промышленных районах, характеризуется негативным влиянием на жителей распространенных токсикантов – тяжелых металлов. В связи с этим, в работе проанализированы данные комплексных исследований, посвященных гигиенической диагностики окружающей среды. С целью оценки влияния свинца и кадмия техногенного происхождения на организм чувствительных групп населения проведен: анализ содержания этих металлов в объектах внешней среды; биомониторинг в крови и моче беременных женщин – жительниц промышленного города Днепропетровска; определение величины их суммарного суточного поступления; рассчет коэффициентов конверсии для характеристики возможных взаимосвязей внешних и внутренних экспозиций ксенобиотиков.